Improving Forehand and Backhand Stroke Learning Outcomes in Table Tennis Through the Discovery Learning Method - Mohamad Fadli; Suriyadi Datau; Ella H. Tumaloto (Jambura Arena Sport, 2025)
Mastery of forehand and backhand strokes is fundamental to student success in table tennis, yet conventional teacher-centered instruction in Indonesian junior high schools often leaves psychomotor learning outcomes below the Minimum Completeness Criterion (KKM), largely because students are rarely given the opportunity to construct stroke technique through guided exploration rather than rote demonstration. This classroom action research examined whether the Discovery Learning method could improve forehand and backhand stroke learning outcomes among 15 eighth-grade students (Class VIII B) at SMP Negeri 1 Kabila, Gorontalo, Indonesia. Using a two-cycle Kemmis and McTaggart design comprising planning, action, observation, and reflection, data were collected through practical skill tests, observation sheets, and documentation, and analyzed descriptively-quantitatively against the KKM. Results showed the mean backhand score rose from 56.81 (13.33% completeness) in Cycle I to 85.22 (100% completeness) in Cycle II, while the mean forehand score rose from 68.76 (33.33% completeness) to 86.42 (100% completeness), corresponding to normalized gains of 0.66 and 0.57, respectively. The novelty of this study lies in demonstrating that structured, teacher-scaffolded discovery cycles, rather than unassisted exploration, can rapidly close the completeness gap in a resource-limited junior high school setting. These findings confirm that Discovery Learning is an effective and replicable alternative for teaching table tennis stroke technique in physical education.